HUBUNGAN ISLAM, HINDU DAN KRISTEN DI INDIA: Studi Terhadap Pemikiran Keagamaan Syaid Ahmad Khan (1817-1898) Dan Abul Kalam Azad (1888-1958) - Saidul Amin (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2014)
Islam, Hinduism and Christianity played significant role in shaping the history of India. The relationship among these three religions have an important place in the history and the future of India. This article would like to explore about this problem based on two Indian Moslem Intellectuals thought: Ahmad Khan and Abul Kalam Azad. The Objective of this research wants to make deeper understanding and respect among the religious people